An augmented reality software suite enabling seamless human robot interaction. Issue 1 (2nd January 2023) - Aivaliotis, Sotiris; Lotsaris, Konstantinos; Gkournelos, Christos; Fourtakas, Nikolaos; Koukas, Spyridon; Kousi, Niki; Makris, Sotiris
ABSTRACT: This paper presents an Augmented Reality software suite aiming at supporting the operator's interaction with flexible mobile robot workers. The developed AR suite, integrated with the shopfloor's Digital Twin, provides the operators' a) virtual interfaces to easily program the mobile robots b) information on the process and the production status, c) safety awareness by superimposing the active safety zones around the robots and d) instructions for recovering the system from unexpected events. The application's purpose is to simplify and accelerate the industrial manufacturing process by introducing an easy and intuitive way of interaction with the hardware, without requiring special programming skills or long training from the human operators. The proposed software is developed for the Microsoft's HoloLens Mixed Reality Headset 2, integrated with Robotic Operation System (ROS), and it has been tested in a case study inspired from the automotive industry.